Analisis Sanitasi Lingkungan Rumah terhadap Indikator Rumah Sehat - Deri Kermelita; Yusmidiarti; Haidina Ali (Poltekkes Kemenkes Semarang, 2026)
Housing and sanitation are important determinants of environmental health and influence healthy housing indicators. Poor sanitation conditions, such as inadequate ventilation, poor lighting, improper waste management, and inadequate wastewater disposal systems, may increase the risk of environment-based diseases. This study aimed to analyze the relationship between housing environmental sanitation conditions and healthy housing indicators in the working area of Muara Bangkahulu Public Health Center, Bengkulu City. This analytic observational study used a cross-sectional design with 72 houses selected through purposive sampling. Data were collected through direct observation using a healthy housing inspection form based on Indonesian Ministry of Health standards and analyzed using the Chi-Square test (α=0.05). The results showed that ventilation, lighting, floor and wall conditions, a healthy latrine, a wastewater disposal system (SPAL), waste management, and residential density were significantly associated with healthy housing status (p<0.05). In contrast, a clean water supply was not (p>0.05). Environmental sanitation plays an important role in preventing environment-based diseases.